Mapping the Global distribution, risk factors, and temporal trends of COPD incidence and mortality (1990–2021): ecological analysis - Shafaq Naeem; Fang Wang; Rabia Mubarak; Hui Shen; Xuechun Li; Irene Mommers; Syeda Rija Hussain; Saima Shakil Malik; Chuanhua Yu; Eelko Hak; Xiaolin Xu; Muhammad Fawad; et al. (BMC Medicine)
Abstract Background Chronic Obstructive Pulmonary Disease (COPD) remains a significant global public health challenge, contributing to substantial morbidity and mortality worldwide. This study aims to analyze global trends in COPD from 1990 to 2021, with a focus on age, sex, and regional variations. By assessing the global burden of COPD and its association with key risk factors, this research provides critical insights into progress toward health-related Sustainable Development Goals (SDGs) and underscores the urgent need to prioritize COPD in public health agendas. Methods Utilizing data from the Global Burden of Disease (GBD) study, this research conducted a comprehensive ecological analysis of COPD epidemiology from 1990 to 2021. Key measures included incidence, mortality, and age-standardized rates, alongside an examination of risk factors such as smoking and ambient particulate matter pollution, quantified using country-level summary exposure values (SEV). Statistical analyses, including descriptive analysis, annual rate of change (ARC), and correlation analysis, were applied to assess the burden of COPD and investigate its ecological associations with major risk factors. Results In 2021, COPD accounted for 16.90 million new cases and 3.70 million deaths globally. The age-standardized incidence rate was 197.37 (95% UI: 181.6–213.42) per 100,000 person-years, while the age-standardized mortality rate was 45.22 (95% UI: 40.61–49.70) per 100,000 person-years. Although global COPD incidence rates declined by 2% from 1990 to 2021, the pace and extent of this decline varied, with some age groups, sexes, and regions experiencing slower reductions or even increases. Higher COPD burden was observed in areas with elevated smoking prevalence, air pollution and greater socioeconomic development. Conclusions This study highlights the ongoing global burden of COPD and its varying trends from 1990 to 2021 across age groups, sexes, and regions. While incidence and mortality rates have slightly declined, disparities persist, particularly among older adults, men, and regions with higher smoking prevalence and air pollution. These findings emphasize the urgent need to integrate COPD into public health priorities, focusing on targeted interventions to reduce key risk factors. Sustained efforts are essential to achieving health-related Sustainable Development Goals (SDGs) and improving global COPD outcomes.